Synergizing Halal Nutrition in Post-Pandemic: Integrating Pedagogy, Canteens, and Indonesia’s Free Nutritious Meals Program - Amalia Rizki Ardiansyah; Sisca Wulandari (Journal of Healthcare and Biomedical Science, 2025)
The COVID-19 pandemic significantly disrupted the dietary habits of elementary school children in Indonesia, triggering a public health concern due to increased consumption of ultra-processed foods. This study examines the integration of halal nutrition and health education as a strategic framework for post-pandemic recovery in school health systems. Using a qualitative exploratory approach, in-depth interviews were conducted with teachers from diverse school environments to analyze the synergy between health education, canteen management, and the Indonesia’s Free Nutritious Meals Program. The findings highlight critical themes: the shift in pediatric consumption patterns, challenges in maintaining public health nutrition standards within school environments, and the pivotal role of teachers in promoting halal-thayyiban principles. The results suggest that integrating these values into the school health infrastructure fosters safe, culturally-sensitive, and sustainable dietary patterns. This integration is vital for the physical and spiritual well-being of the younger generation, bridging the gap between religious values and holistic health outcomes. While limited by a small sample size, this research underscores the necessity of multi-sectoral collaboration to strengthen school-based health interventions. The study’s originality lies in its comprehensive approach to halal nutrition as a foundation for building a resilient national health system in the post-pandemic era.